Integrating health services into microfinance operations for sustainable poverty alleviation: the case of female clients in Edo State (2014)
Microfinance role in women empowerment and poverty alleviation has received a lot of focus with negligible attention on health implications. This paper focuses on microfinance and health- integration services as pathway for sustainable poverty alleviation, using cross-sectional survey of 750 purposively selected respondents (400 from micro finance banks (MBs) with integrated health-related services (IHS) and 350from MBs without IMS in Benin, Ugbowo, Iruekpen, Auchi, Jattu and Ekpoma. Fourteen In-depth interviews and 20 Key Informant Interviews were conducted. Respondents (60.3%) from MBs with IHS, who attached high importance to their health, doubled those from MBs without IHS (30.3%). IHS enabled client:: practice preventive health behaviour and payment for health services. IHS helps women value their health and reduces health-risks. MBs should be encouraged and funded to integrate health-related services in their operations.